2017
DOI: 10.1002/bjs.10415
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of carbohydrate antigen 19-9 in patients undergoing resection of biliary tract cancer

Abstract: Non-normalization of CA19-9 level after resection of BTC with curative intent was associated with worse OS. R1 resection was associated with a particularly poor prognosis when CA19-9 levels did not normalize.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
53
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 27 publications
2
53
2
Order By: Relevance
“…Chung et al also showed that high preoperative CA19‐9 (>55 U/mL) was an independent predictor of a high risk of recurrence . On the other hand, Yamashita et al suggested that patients with high preoperative CA19‐9 that was normalized after resection had a similar OS compared with those of initially normal preoperative CA19‐9, which meant postoperative level was more relevant . Thus in extrahepatic cholangiocarcinoma, the association of preoperative CA19‐9 itself with tumor burden or prognosis requires further study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Chung et al also showed that high preoperative CA19‐9 (>55 U/mL) was an independent predictor of a high risk of recurrence . On the other hand, Yamashita et al suggested that patients with high preoperative CA19‐9 that was normalized after resection had a similar OS compared with those of initially normal preoperative CA19‐9, which meant postoperative level was more relevant . Thus in extrahepatic cholangiocarcinoma, the association of preoperative CA19‐9 itself with tumor burden or prognosis requires further study.…”
Section: Discussionmentioning
confidence: 99%
“…However, not all patients will likely derive benefits from adjuvant CRT, and current guidelines based on several retrospective studies do not address personalized care. Previous studies suggested that it was reasonable to consider adjuvant therapy in patients with high preoperative CA19‐9 level that was not normalized after surgery . Previous meta‐analysis suggested the role of adjuvant therapy in patients with N1 disease and R1 resection .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, there are no established methods to define patient subgroups that need adjuvant strategies. The preoperative measurement of serum tumor markers may identify high-risk patients; however, few studies have investigated biomarkers in patients with ICC possibly due to the difficulties associated with collecting large numbers of serum samples from patients with ICC (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%